2019
DOI: 10.1016/j.xphs.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Intracellular Accumulation and Retention of Lysosomotropic Macrocyclic Compounds by High-Throughput Imaging of Lysosomal Changes

Abstract: Many marketed pharmaceuticals reach extremely high tissue concentrations due to accumulation in lysosomes (lysosomotropism). Quantitative prediction of intracellular concentrations of accumulating drugs is challenging, especially for macrocyclic compounds that mainly do not fit in current in silico models. We tested a unique library of 47 compounds (containing 39 macrocycles) specifically designed to cover the entire range of accumulation intensities observed with pharmaceuticals so far. For the first time, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The mentioned drugs, chloroquine, hydroxychloroquine and azithromycin, highly accumulate in lysosomes/endosomes and their membranes, reaching about 100-fold higher intracellular than their extracellular concentration [ 7 , 8 ], and thus belong to a group of lysosomotropic compounds (compounds that accumulate in lysosomes). We propose that the antiviral activity of (hydroxy)chloroquine and azithromycin is shared among all strong lysosomotropic drugs and is a consequence of their extremely high accumulation in cells and membranes, and subsequently of all the processes affected by this pharmacokinetic property.…”
Section: Antiviral Effects Of Highly Accumulating Lysosomotropic Drugmentioning
confidence: 99%
See 3 more Smart Citations
“…The mentioned drugs, chloroquine, hydroxychloroquine and azithromycin, highly accumulate in lysosomes/endosomes and their membranes, reaching about 100-fold higher intracellular than their extracellular concentration [ 7 , 8 ], and thus belong to a group of lysosomotropic compounds (compounds that accumulate in lysosomes). We propose that the antiviral activity of (hydroxy)chloroquine and azithromycin is shared among all strong lysosomotropic drugs and is a consequence of their extremely high accumulation in cells and membranes, and subsequently of all the processes affected by this pharmacokinetic property.…”
Section: Antiviral Effects Of Highly Accumulating Lysosomotropic Drugmentioning
confidence: 99%
“…In our previous studies on a set of 47 compounds we have shown that the extent of lysosomotropic accumulation in cells correlates with the compound’s extent of induction of phospholipidosis and lysosomal swelling [ 7 ]. The correlation is so apparent that it is even possible to determine the level of accumulation from the intensity of either of these processes caused by a drug.…”
Section: Antiviral Effects Of Highly Accumulating Lysosomotropic Drugmentioning
confidence: 99%
See 2 more Smart Citations
“…Gulbins et al, 2018 [20] Guan et al, 2019 [21] Lee et al, 2013 [22] Easwaranathan et al, 2019 [23] Azithromycin (antibiotic) Strong cationic amphiphilic drug.…”
Section: Name and Basic Functions Of The Drug Or Compound Biological mentioning
confidence: 99%